Forensic Nursing and Mental Disorder in Clinical Practice - Norman Mc Clelland, Martin Humphreys, Lorraine Conlon, Tony Hillis (Butter worth Heinemann, 2001)
Buku ini berisi tentang Perawatan Forensik dan Gangguan Mental dalam Praktek Klinis